2022
DOI: 10.3389/fsurg.2022.894662
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous full-endoscopic uniportal decompression for the treatment of symptomatic idiopathic lumbar spinal epidural lipomatosis: Technical note

Abstract: BackgroundLumbar spinal epidural lipomatosis (SEL) is a rare condition characterized by an excessive accumulation of adipose tissue within the spinal canal, compressing the dura sac and/or nerve roots. When conservative treatments fail and clinical symptoms progress quickly and seriously, surgical decompression should be considered. With the rapid development of endoscopic armamentaria and techniques, the pathological scope that can be treated by percutaneous endoscopic spine surgery is ever expanding.Objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Conditions such as disc degeneration, central lumbar stenosis, lumbar foraminal stenosis, and lumbar spondylolisthesis are all now amenable to endoscopic treatment ( 19 ). Yu et al ( 20 ) documented the successful treatment of a patient with symptomatic SEL through percutaneous full-endoscopic uniportal decompression.…”
Section: Discussionmentioning
confidence: 99%
“…Conditions such as disc degeneration, central lumbar stenosis, lumbar foraminal stenosis, and lumbar spondylolisthesis are all now amenable to endoscopic treatment ( 19 ). Yu et al ( 20 ) documented the successful treatment of a patient with symptomatic SEL through percutaneous full-endoscopic uniportal decompression.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that single-channel spinal endoscopy exhibits optimal short-term clinical efficacy for treating LEF; however, it has a small operation space, narrow decompression range, difficult operation, and steep learning curve. These deficiencies limit the clinical application of single-channel endoscopy for LEF treatment ( 12 , 13 ). Bilateral decompression is frequently required in patients with LEF complicated by severe lumbar spinal stenosis.…”
Section: Introductionmentioning
confidence: 99%